Seasonal variation of catch per unit effort and catch composition in a Persian Gulf longline fishery - SEYED YOUSEF PAIGHAMBARI; MORTEZA EIGHANI (Biodiversitas Journal of Biological Diversity, 2018)
Paighambari SY, Eighani M. 2018. Seasonal variation of catch per unit effort and catch composition in a Persian Gulf longline fishery. Biodiversitas 19: 888-892. The catch per unit effort (CPUE), and catch composition of a Persian Gulf longline fishery were investigated during the study to develop essential information regarding the needs of longline fishing in Persian Gulf just to assist the artisanal fishermen. A total number of 2990 deployed hooks were set during spring and winter seasons. One catch contained 8 teleost fish and one elasmobranch species belonging to 8 families. In the spring season, 357 fish were counted during sampling out of which Netuma thalassina with 183 specimens (F= 51.3%) was the most abundant one. In winter season 235 specimens were collected, of which 17.7% were represented by the N. thalassina. So, there is no significant difference in fish assemblages were obtained between spring and winter seasons (R=0.567, P>0.05). Proportion of all caught fish below length at maturity was higher in the winter season than spring season. Data revealed significantly higher CPUE at spring season compared to winter (P<0.05), suggesting that in general, fishing at the spring season was necessarily more efficient than winters. Difference in CPUE between spring and winter seasons may be explained by the species response to the temperature cycle in the Persian Gulf. A better understanding of the complete catch including catch rate, catch composition, and their sizes, is therefore, an important step towards a sustainable Persian Gulf longline fishery.